Enhancing Career Readiness through Mock Interview Training and Structured Feedback - Lestari Adhi Widyowati; Inta Hartaningtyas Rani; Jara Hardiyanti Jalih (ADI Pengabdian Kepada Masyarakat, 2026)
Vocational school students need more than simply technical skills as they are in the transition phase into the workforce. Today’s recruitment places communication skills, the ability to narrate experiences, and professional ethics as the main determinants of interview success. The phenomena shows that there is a skills gap between industry needs and the readiness of early graduates, particularly at the interview and self-presentation stages. This community service is designed to fill this gap through a series of interactive job readiness workshops. The course covers an introduction to professional branding, compiling CVs that are relevant to industry standards, and strategies for addressing interview questions. The programme facilitates structured mock interviews with practitioners, giving students exposure that closely reflects real-world recruitment settings. Each participant receives feedback on their strengths and areas for improvement, both in content, body language, and communication style. The significance of the pre- and post-test results indicates an improvement in students’ understanding and readiness after participating in the workshop. The programme is expected to bridge classroom learning and workplace recruitment expectations. Organised by ITB Ahmad Dahlan in collaboration with SMK Muhammadiyah 1 Ciputat, this activity also strengthens the school–campus network in nurturing young talent who are not only technically skilled but also ready for the workforce.